Eocene Neo-Tethyan slab breakoffconstrained by 45 Ma oceanic island basalt-type magmatism in southern Tibet - Ji, W.; Wu, F.; Chung, S.; Wang, Xuan-Ce; Liu, C.; Li, Q.; Liu, Z.; Liu, X.; Wang, J. (Geological Society of America, 2016)
Slab breakoffis one of the primary processes in the evolution of many collisional orogens. In the Tibet-Himalaya orogen, the timing of breakoffof the Neo-Tethyan slab remains controversial because of a scarcity of solid evidence. This study reports the discovery of Eocene gabbros, dated at 45.0 ± 1.4 Ma (in situ U-Pb age of titanite) using secondary ion mass spectrometry, from the eastern segment of Tethyan Himalaya in southern Tibet. These rocks show geochemical characteristics similar to those of HIMU (high µ)-type oceanic island basalt and have depleted Sr-Nd isotopes [87Sr/86Sr(t) = 0.70312-0.70317; eNd(t) = +4.9 to +5.0]. It is suggested that the gabbros stand as the first direct evidence for partial melting of the asthenosphere followed by rapid magma ascent with negligible crustal contamination. This event, combined with results from relevant studies along the Indus-Yarlung suture zone, is best explained by a sudden and full-scale detachment of subducted Neo-Tethyan slab at great depth. The breakoffmodel may account for coeval tectonomagmatic activities (development of small-scale, short-lived magmatism and subsequent termination of the Gangdese arc magmatism) in southern Tibet and for the abrupt slowdown (ca. 45 Ma) of Indo-Asia convergence.